Laparoscopic ventral hernia mesh repair without the use of transfascial sutures: our experience - D., Wasim M.; Muddebihal, Uday; Rao, U. V.; J., Praveen (International Surgery Journal, 2018)
Background: Repair of the abdominal wall defects can be quite challenging even for most experienced surgeon under best of conditions. In the laparoscopic method there have been many modifications with regard to the type of mesh and methods of fixation. The aim of this study was to identify immediate post-operative pain and the long-term outcomes of laparoscopic ventral hernia mesh repair without the use of transfascial sutures to fix the mesh. Methods: A total of hundred (n=100) patients underwent Laparoscopic Ventral Hernia Mesh Repair by our surgical unit between January 2011 and December 2015. All patients underwent standardized Laparoscopic mesh repair with light weight composite meshes and without the use of transfascial sutures. Only absorbable tackers were used to anchor the mesh. Analgesics stopped after 24 hours or given only on demand. Mesh fixation time, post-operative pain score (visual analogue score), and follow up for pain and recurrence (at 6 months, 12 months and 24 months) were recorded and analyzed. Results: Out of 100 patients (42 men and 58 women), the mean age was 48 years and BMI of the patients was 20-35. Types of hernias operated were 63 para umbilical hernias, 32 incisional and 5 recurrent hernias. The median defect size was 5 cm (Range 3-8 cm) and the mesh sizes used were15 x 15 cm circular (87) and 15 x 20 rectangular (13). The median mesh fixation time with only absorbable tackers was 15 mins (range 15-20 mins). Visual analog scale for pain (VAS) was of median 1 (Range 0-2) at 24 hours. Five patients required analgesics for 48 hours. No patients complained of pain at follow ups (1 month, 6 months, 12 months and 24 months). Mean hospital stay post operatively was 2-3 days. Only one patient had recurrence of hernia within 6 months Conclusions: Laparoscopic Ventral Hernia Mesh Repair without the use of transfascial sutures is an easy and feasible approach. The use of only absorbable tacks to fix the mesh is time saving and gives less post-operative pain. However, randomized controlled trials are required to compare transfascial sutures with absorbable tacks for fixing the mesh in separate cases to reach a standardized method.